The machines optimal set development for the construction of automotive roads elements based on the "Norm" for machines employment cost - Maksudov Zokir (E3S Web of Conferences, 2021)
Currently, increasing the efficiency of using the fleet of cars and the functioning of a road enterprise for the construction of highways by forming an optimal set of machines based on the developed normative labor intensity and the production of road construction vehicles for the construction of elements of highways, in a mixed fleet of vehicles of a road enterprise, is a very relevant task. A technique has been developed for optimizing a set of machines for the construction of road elements based on the "norm" of the labor input of the machines. Methodology for standardizing the production of road equipment and calculating the optimal set of vehicles based on the production rate of vehicles for the construction of road elements has been developed. A system of machines has been developed to form a set of machines to construct road elements. Nomograms have been developed for determining and forming the optimal set of machines for the construction of road elements based on the "norm" of the labor input of machines.